2020
DOI: 10.1177/2331216520956560
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aging and the Electrode-to-Neural Interface on Temporal Processing Ability in Cochlear-Implant Users: Gap Detection Thresholds

Abstract: Accurate processing of temporal information is critical to understanding speech through a cochlear implant (CI). This has potential implications for the growing population of CI users who are ≥65 years of age because of age-related auditory temporal processing deficits. The goal of this study was to measure temporal processing ability in a gap detection task in younger, middle-aged, and older CI users and to determine the relative contributions of chronological age and peripheral neural survival to performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 49 publications
4
19
0
Order By: Relevance
“…Specifically, the middle-aged adults had significantly greater slopes than the elderly adults. This result is consistent with the previously reported age-related decline in slope of the eCAP AGF in the literature (Cafarelli Dees et al 2005; Jahn & Arenberg 2020b; Mussoi & Brown 2020; Shader et al 2020). Overall, these studies provide strong evidence that the slope of the eCAP AGF is negatively affected by advanced age.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, the middle-aged adults had significantly greater slopes than the elderly adults. This result is consistent with the previously reported age-related decline in slope of the eCAP AGF in the literature (Cafarelli Dees et al 2005; Jahn & Arenberg 2020b; Mussoi & Brown 2020; Shader et al 2020). Overall, these studies provide strong evidence that the slope of the eCAP AGF is negatively affected by advanced age.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, psychophysical measures were conducted using long-duration pulsatile stimulation. In contrast, the AN function was quantified based on either the slope of the eCAP input/output function (Shader et al 2020a(Shader et al , 2020bJohnson et al 2021) or the time constant estimated based on the eCAP HE ET AL. / EAR & HEARING, VOL.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the predictive validity of ECAP AGFs to temporal processing appears to be inconsistent with some of the extant literature ( Hay-McCutcheon et al., 2005 ; Hughes et al., 2014 ; Shader et al., 2020a ). However, consistent with our results, Shader et al. (2020a) found that steep ECAP AGF slopes were not predictive of better temporal processing as measured by an amplitude modulation detection task.…”
Section: Discussionmentioning
confidence: 71%
“…It should be noted that the predictive validity of ECAP AGFs to temporal processing appears to be inconsistent with some of the extant literature (Hay-McCutcheon et al., 2005; Hughes et al., 2014; Shader et al., 2020a). However, consistent with our results, Shader et al.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation